Diaspora as a Distinct Site of Translational Activity: The Case of U.S. Immigrant Newspapers, 1917-1941 - Baer, Brian; Pokorn, Nike (TTR, 2018)
This article argues for the study of translation in U.S. immigrant newspapers, a distinct intercultural context largely ignored in Translation Studies research. The article outlines methodological approaches for the study of translation in immigrant periodicals with the aim of identifying the various roles played by translation in diasporic communities. Based on approaches and methods developed in the field of Translation Studies for researching translation in newspapers, the analysis focuses on the (in)visibility of the translations, the direction of translation flows, and the domain of the translated texts. These categories contribute to our understanding of diaspora as a distinct site of translational activity, through which immigrant identities are constructed and relationships between the immigrant community and the dominant culture, between the immigrant community and its native language and culture, and between different generations within the immigrant community, are negotiated. Preliminary research of two immigrant foreign-language newspapers published in the U.S. in the interwar period, the Slovenian Prosveta, and the Russian Novoe Russkoe Slovo, has documented a consistent presence of translations. The results suggest that translation in these two newspapers was deployed to different ends, reflecting the divergent political orientations of the newspapers and the distinct make-up of these immigrant communities. The study also reveals translation to be a tool of government surveillance.